Deep neural networks enable quantitative movement analysis using single-camera videos - Łukasz Kidziński (Nature Portfolio, 2020)
In the context of diseases impairing movement, quantitative assessment of motion is critical to medical decision-making but is currently possible only with expensive motion capture systems and trained personnel. Here, the authors present a method for predicting clinically relevant motion parameters from an ordinary video of a patient.